2009
DOI: 10.1377/hlthaff.28.6.w1110
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Labeling And Food Choices: A First Look At The Effects On Low-Income People In New York City

Abstract: ABSTRACT:We examined the influence of menu calorie labels on fast food choices in the wake of New York City's labeling mandate. Receipts and survey responses were collected from 1,156 adults at fast-food restaurants in low-income, minority New York communities. These were compared to a sample in Newark, New Jersey, a city that had not introduced menu labeling. We found that 27.7 percent who saw calorie labeling in New York said the information influenced their choices. However, we did not detect a change in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
333
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(356 citation statements)
references
References 33 publications
13
333
4
3
Order By: Relevance
“…For instance, to combat the so called "obesity epidemic" in the US, the ("Obamacare") Patient Protection and Affordable Care Act of 2010 has mandated that, starting in 2013, chain restaurants post calorie counts on their menus. But studies of a similar mandate enacted by New York City in 2008 have found that menu labeling has little or no impact on food consumption (Borgmeier and Westenhoefer, 2009;Elbel et al, 2009Elbel et al, , 2011Vadiveloo et al,2011). Strategic self-ignorance could help explain why labeling does little to encourage healthier choices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, to combat the so called "obesity epidemic" in the US, the ("Obamacare") Patient Protection and Affordable Care Act of 2010 has mandated that, starting in 2013, chain restaurants post calorie counts on their menus. But studies of a similar mandate enacted by New York City in 2008 have found that menu labeling has little or no impact on food consumption (Borgmeier and Westenhoefer, 2009;Elbel et al, 2009Elbel et al, , 2011Vadiveloo et al,2011). Strategic self-ignorance could help explain why labeling does little to encourage healthier choices.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Americans now consume an estimated one third of their total calories 3 and spend almost half their annual food dollars on foods prepared outside the home. 4 Consumers, however, are generally unaware of, or inaccurately estimate, the number of calories in restaurant foods.…”
Section: Introductionmentioning
confidence: 99%
“…Although the FDA has been thorough and thoughtful in the solicitation and consideration of stakeholder comments, it remains a problematic challenge, because published research to date has produced inconsistent findings about the ideal format and overall efficacy of calorie postings in restaurants. 2,5,[6][7][8][9][10][11][12][13][14][15][16][17][18] For example, two recent studies in adjoining counties in Washington State produced inconclusive results. Pulos and Leng 17 evaluated the calorie content of meals ordered before and after menu labeling laws were instituted in Pierce County (population 814,600), revealing significant differences in food purchasing behavior with a reduction in calories purchased after the menu-posting legislation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several possible reasons for that: First, people only chose items for themselves in this experiment (no sharing or orders for multiple people); second, most menus excluded drinks (a decision made for feasibility given time constraints); and finally, only the Pizza and Mexican menus allowed for ordering multiple items. For comparison, Dumanovsky et al (2011) and Elbel et al (2009) report means of 800 kcal in fast-food restaurants. Using data from a large coffee chain, Bollinger, Leslie, and Sorensen (2011) report average drink calories per transaction of 143 kcal, slightly below the average in our experiment.…”
Section: Food Selection and Response Patternsmentioning
confidence: 99%